2017
DOI: 10.1016/j.cell.2017.03.035
|View full text |Cite
|
Sign up to set email alerts
|

mTOR Signaling in Growth, Metabolism, and Disease

Abstract: The mechanistic Target of Rapamycin (mTOR) coordinates eukaryotic cell growth and metabolism with environmental inputs including nutrients and growth factors. Extensive research over the past two decades has established a central role for mTOR in regulating many fundamental cell processes, from protein synthesis to autophagy, and deregulated mTOR signaling is implicated in the progression of cancer and diabetes, as well as the aging process. Here, we review recent advances in our understanding of mTOR function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

42
2,611
1
24

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 2,272 publications
(2,678 citation statements)
references
References 107 publications
(115 reference statements)
42
2,611
1
24
Order By: Relevance
“…Nutrient and growth factor pathways regulate the cellular metabolism and protein synthesis by regulating the activity of mTORC1 [12]. Aberrant mTORC1 activation is common in cancer, and mTORC1 signaling promotes cancer progression by stimulating pathways that in turn support cancer cell growth, proliferation and resistance to apoptosis [12].…”
Section: Lat1 Promotes Mtorc1 Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Nutrient and growth factor pathways regulate the cellular metabolism and protein synthesis by regulating the activity of mTORC1 [12]. Aberrant mTORC1 activation is common in cancer, and mTORC1 signaling promotes cancer progression by stimulating pathways that in turn support cancer cell growth, proliferation and resistance to apoptosis [12].…”
Section: Lat1 Promotes Mtorc1 Activitymentioning
confidence: 99%
“…Aberrant mTORC1 activation is common in cancer, and mTORC1 signaling promotes cancer progression by stimulating pathways that in turn support cancer cell growth, proliferation and resistance to apoptosis [12]. In regards to amino acids, leucine is the most effective activator of mTORC1 [12]. Leucine stimulates the translocation of mTORC1 to the surface of the lysosome, which is the site of mTORC1 activation [12].…”
Section: Lat1 Promotes Mtorc1 Activitymentioning
confidence: 99%
“…Signals from bioenergetics status, oxygen levels, DNA damage, and amino acids availability converge on mTOR, unleashing a series of metabolic responses [18]. In fact, it has been shown that mTOR, when incorporated in mTORC1, promotes the synthesis of proteins, lipids, and nucleotides, as well as the adoption of a glycolytic phenotype, and an increase of carbon flux in the pentose phosphate pathway [18,19]. Indeed, research efforts in the leukemia setting have been mainly focused on the glycolytic aspect, in an attempt to exploit this feature as a target for therapeutic intervention.…”
Section: Mtor Involvement In Leukemia Metabolismmentioning
confidence: 99%
“…The overall rate of protein synthesis also depends on the number of ribosomes, and TORC1 also enhances the synthesis of ribosomal proteins and RNA (30). TORC1 promotes lipid synthesis by activating SREBP (sterol responsive element binding protein) (38).…”
Section: General Functioning Of the Mtor Pathwaymentioning
confidence: 99%
“…mTOR is the target of the anti-fungal metabolite rapamycin. It is named after the island Rapa Nui (Easter Island) from whose soil it was first isolated and has broad antiproliferative and immunosuppresive properties (38). Genetic screens in the early 1990's in yeast identified two genes TOR1 and TOR2 that mediated the effects of rapamycin.…”
Section: General Functioning Of the Mtor Pathwaymentioning
confidence: 99%